Using Men's Changing Rooms When You Haven't Got a Penis: The constitutive potential of performing transgendered masculinities. (9th August 2012) - McNamara, Catherine
This article is a consideration of the ways that transgender performers and queer bodies in performance contribute to the ongoing formation of the category of gender. It explores the relationship between performing transgendered masculinities and the constitutive potential of the law (namely the Gender Recognition Act 2004) surrounding (trans)gender identity. The article looks at examples of performance by transgender performance artists, Jason Barker staged as part of the annual Transfabulous International Festival of Transgender Arts in 2006 and 2007 and Lazlo Pearlman in He Was a Sailor, the Sea Was Inside Him (Drill Hall, London, 2007). Trans and queer performance work is still, for the most part, left out of academic discourse within performance studies. Engaging with trans art and trans artists in relation to shifts in legislation around gender brings very specific readings into the public domain. This record of performance that takes place beyond the mainstream brings transgender and genderqueer performance practice to the fore.